2019
DOI: 10.1177/1077699019857693
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying Panic and Facilitating Prevention: Multifaceted Effects of Traditional and Social Media Use During the 2015 MERS Crisis in South Korea

Abstract: In the context of the 2015 Middle East respiratory syndrome (MERS) outbreak in South Korea, this study examines the multifaceted effects of media use considering the current complex media environment. Analysis of a two-wave online panel survey found that traditional media use had a positive influence on MERS knowledge while social media use did not. However, knowledge did not facilitate preventive behaviors. In contrast, negative emotional responses due to media use stimulated desirable behaviors. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 55 publications
6
69
1
1
Order By: Relevance
“…Moreover, exposure through official media channels had a positive impact on hand hygiene, while exposure through unofficial media channels and face-to-face communication had no impact or even a negative impact on the same behavior. Previous studies suggested that the more people read newspapers and watched television reports about MERS, the more knowledge they acquired about the disease and its prevention strategies [ 22 , 23 ]. Compared to official media channels, which mainly report information verified by expert sources, unofficial web-based media channels and face-to-face communication can disseminate not only knowledge but also false or unverified information during a crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exposure through official media channels had a positive impact on hand hygiene, while exposure through unofficial media channels and face-to-face communication had no impact or even a negative impact on the same behavior. Previous studies suggested that the more people read newspapers and watched television reports about MERS, the more knowledge they acquired about the disease and its prevention strategies [ 22 , 23 ]. Compared to official media channels, which mainly report information verified by expert sources, unofficial web-based media channels and face-to-face communication can disseminate not only knowledge but also false or unverified information during a crisis.…”
Section: Discussionmentioning
confidence: 99%
“…During the Middle East respiratory syndrome (MERS) outbreak, increased exposure to MERS-specific information through social media and interpersonal communication was associated with higher adoption of personal preventive measures. However, the association between exposure to information disseminated through traditional media (eg, television and newspapers) and personal preventive measures was nonsignificant [ 22 , 23 ]. At the social-structural level, implementation of organizational preventive measures during work resumption may differ across factories, which may also affect compliance with personal preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…During public health emergencies, the media is an essential tool used by government and public health authorities to manage crises [ 2 ], and the public relies on media to understand the situation [ 3 ]. Infectious disease pandemics, such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) trigger spontaneous and intensive media attention, which could have effects on various public responses [ 4 , 5 ]. One of the most desirable public responses is the adoption of personal preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Universal face mask wearing [ 6 ] and hand hygiene [ 7 ] are strongly advocated by the World Health Organization (WHO) and have been widely implemented during the COVID-19 pandemic [ 8 , 9 ]. Media exposure has been demonstrated to increase health knowledge among the public, which in turn encourages desirable preventive behaviors during infectious disease pandemics [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A intensa incerteza inerente a uma situação de crise galvaniza o medo, a preocupação e o pĂąnico (3) . Pesquisas anteriores indicam que os indivĂ­duos geralmente se sentem mais ameaçados durante as crises do que o exigido pelo nĂ­vel de risco real (4) .…”
Section: Introductionunclassified